Richness and density of echinoderms in the rocky reefs of Punta Amapala, El Salvador - Figueroa Segovia, Laura Liseth; Segovia-Prado, Johanna (Revista de Biología Tropical, 2024)
Introduction: Echinoderms are strictly aquatic animals and one of the groups of marine invertebrates whose ecological importance is crucial for the environments where they inhabit. The most outstanding characteristic is their pentaradial symmetry. These organisms can be distributed in a wide variety of oceanic environments, and are not exclusive inhabitants of reef formations. A total of 1 539 species have been registered, of which 717 belong to the Pacific and 60 of them have been registered for El Salvador. Objective: The objective of the work was to record the richness and density of echinoderm species in rocky reefs of Punta Amapala (La Unión). Methods: The sampling was conducted in five sites, two of them at 3 m of depth and three at 6 m. For this, snorkeling and autonomous diving were used, covering two band transects of 30 x 1 m. Within the transects, the identification (richness) and counting (abundance) of the organisms was carried out. Results: The species that presented the highest density at 3 m reefs was Echinometra vanbrunti (0.83 indv/m2), followed by the ophiuroid Ophiocomella alexandri (0.16 indv/m2) and Ophiocoma aethiops (0.16 indv/m2). And at the 6 m reefs were Ophiothela mirabilis (0.83 indv/m2), Ophionereis annulata (0.21 indv/m2), Ophiothrix rudis (0.08 indv/m2) and Ophiocomella alexandri (0.01 indv/m2). Conclusions: These organisms fulfill various ecological roles, such as being bioindicators of water quality by tolerating certain changes in physicochemical conditions and fulfilling the role of macrofauna hosts due to the cavities formed by some sea urchins. That is why sampling efforts must increase in these areas to monitor the quality and health of the rocky reefs, whose role is key, as they are, together with Los Cóbanos, the largest in the country.